Role of Abscisic Acid in The Water Balance of Pistachio (Pistacia. vera) Seedlings - Alabdullah, Ibrahim Mohammad; Daire, Muhammad Ayman; Kardoush, Mohamad; Twaklna, Mhasen (Journal of agricultural, environmental and veterinary sciences, 2021)
This experiment aims to study the effect of abscisic acid in maintaining water balance under different levels of irrigation. it was carried out in Pistachio Office on two-years-old (P.vera) seedlings growing in polyethylene bags. Three irrigation and three abscisic acid treatments were applied during 2019 and 2020 year. The results showed a significant change of water stress on most of the growth indicators (planting length - planting diameter - leaf area, etc.) which decreased and reached its lowest value when irrigation with 14-day interval between irrigation. As for abscisic acid treatments reduced significantly and avoided the harmful effects of water stress and improved the water balance of seedlings. A significant increase was observed in length of the main axis of seedlings that treated with abscisic acid (59.3 cm) compared with control plants (55.5cm) under water stress conditions, in addition to it was observed an increase in concentration of chlorophyll (38 mg/ g ww) compared to control plants (36.19 mg/ g ww), while the level of proline in the treated plants increased significantly (52.5 mg/ g ww) compared with untreated control plants (50 mg/ g ww), and these results illustrate the important role of abscisic acid in regulating water relations within the plant. And increase the plant’s ability to withstand the negative effects of water stress.